PROBLEMATIKA PENGGANTIAN CALON KEPALA DAERAH YANG MENINGGAL DUNIA SEBELUM HARI PEMUNGUTAN SUARA - Nasution, Ali Imran; Ahmad Reihan Thoriq (Fakultas Hukum, Universitas Islam Balitar, 2025)
This study aims to analyze the legal problems concerning the replacement of a candidate pair or one of the candidates for regional head who passes away within 30 and 29 days prior to election day. This research employs a normative juridical method through statutory, conceptual, and comparative approaches. The findings demonstrate that the death of a candidate pair or one of the candidates for regional head, occurring with a one-day difference between 30 and 29 days before election day, results in the loss of the right of political parties or coalitions to nominate a replacement candidate. Therefore, it is necessary to amend Article 54 of Law No. 10 of 2016 to establish a single deadline for the nomination of replacement candidates, in order to ensure legal certainty and the continuity of regional head elections.